BAKTERI PENGHASIL BIOSURFAKTAN YANG DIISOLASI DARI PULAU LAKI KEPULAUAN SERIBU - Riffiani, Rini (Jurnal Hidrosfir Indonesia, 2010)
Biosurfactants are the surface-active molecules synthesized by microorganisms. The microbial surfactant were interesting because of the biodegradable and have many application in industry. With the advantage of environmental compatibility, the demand for biosurfactants has beensteadily increasing and may eventually replace their chemically synthesized counterparts. Marine biosurfactants produced by some marine microorganisms have been paid more attention particularly for the bioremediation of the sea polluted by crude oil. The aim of this research isto screening microorganisms that produce biosurfactant from Pulau Laki, Kepulauan Seribu, Jakarta. The isolate which produce biosurfactant showed by clear ring zone on ONR7a crude oil medium. Three isolates were identified their characteristics based on the composition of nitrogenbase. Molecular identification based on 16S rRNA gene sequences indicated that bacteria had the highest similarity with Marinobacter satoriniensis strain NKSGI, Paracoccus sp and Pseudomonas sp.